Feature analysis of the second generation standard DVB-S2 for satellite broad-band services - Alizadeh, Abdolhadi (Видавництво Львівської політехніки, 2010)
This paper describes the next Generation Solution for both SDTV and HDTV distribution system. It is based on the new emerging DVB-S2 Standard, which enables a much more efficient transmission of digital video in current Satellite Transponders. The new Technology dramatically improves utilization of the available satellite bandwidth which will enable increased programming capacity, increased geographical coverage of the satellite footprint (more customers) and accommodate future requirements for high definition TV (HDTV).
Keywords: DVB-S2; HDTV; APSK; Forward error correction(FEC); Adaptive coding and modulation (ACM)